An Investigation of Density and Thickness of Geopolymer Concrete as Gamma Ray Radiation Shielding Application - MARZUKI, NUR NADIRA SYAHIRAH (Enhanced Knowledge in Sciences and Technology, 2023)
This study focused on the investigation of the density and thickness of geopolymer (GP) which consist of various material including, sand, clay, brick, cement, ceramic, and granite as their primary composition. The objectives of the prepare a GP concrete with different ratios and percentages of material, are to investigate the interaction of gamma rays with GP according to its density and to optimize the thickness of GP concrete for Cobalt-60 radiation. The materials were dried under sunlight before grinded, sieved, and compressed into the form of a pallet. The GP pallets were then sintered before being aimed with Cobalt-60. There are 2 different instruments to identify the physical properties of GP including the thickness and density of GP prepared. OD-02 survey meter was used to identify dose rate analysis. GP 6 and 10 were revealed to have the ability to perform gamma-ray radiation shielding depending on their density and thickness of GP.